A FRACTIONAL MODEL PREDICTIVE CONTROL DESIGN FOR 2-D GANTRY CRANE SYSTEM - ABHAYA P. SINGH; H. AGRAWAL (Journal of Engineering Science and Technology, 2018)
Fractional calculus has been a research focus since the last four decades to control the dynamical systems. Advances in fractional calculus such as Fractional Model Predictive Control had shown that system dynamics could be controlled even more effectively. This paper proposes Fractional Model Predictive Control design for a 2-D gantry crane system (a robotic manipulator). 2-D gantry crane system is an under-actuated system with two degrees of freedom and single control input. The model is derived using Euler-Lagrange formulation and the corresponding fractional model is embedded, further, this model is approximated using an Oustaloup-Recursive-Approximation for different fractional values. A Fractional Model Predictive Controller and a traditional Model Predictive Control for the 2-D Gantry crane system are designed using MPC toolbox of MATLAB. This controller gives a better response in terms of systems settling time and overshoot in the system. Further, the performances of these controllers are compared with other existing controllers. The purpose of these controllers here is to control the position of the trolley and the swing angle of the cable through which the load is suspended.